(untitled) (Linguostylistic Studies, 2015)
The article presents the study of the official business discourse as communicatively unilateral genre of communication in public-political, legal and social and economic life of the society, defining its intentional dominant – intention of regulation which has a distinct antropooriented and imperative character. Status and role differentiation of the officially-business discourse is the basis for highlighting three genre manifestations of intentions of regulation. Specifically, the article describes intentions explicated in legal documents, and intentions in the field of diplomatic relations; the system of discursive-marked means of placing emphasis on a particular intention (declarative utterances, stereotyped expressions, incentive constructions, performatives, I-statements and constructs of speech etiquette). Key words: communicative intention, speaker, official business discourse, genre, style, syntactic constructions. References